1999
DOI: 10.1002/hep.510300118
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-associated TT virus infection and its relationship to liver disease

Abstract: TT virus (TTV) has been proposed as the causative agent of non-A to E hepatitis. We studied the association between TTV viremia and biochemical evidence of hepatitis in blood donors and prospectively-followed patients. TTV was found in 7.5% of 402 donors and in 11.0% of 347 patients before transfusion. The rate of new TTV infections was 4.7% in 127 nontransfused, and 26.4% in 182 transfused patients (P F .0001). The risk of infection increased with the number of units transfused (P F .0001). The rate of new TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
1
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 24 publications
5
70
1
8
Order By: Relevance
“…TTV was fi rst detected in subjects with post-transfusion hepatitis and indicated as a possible etiological source of non A-non C hepatitis 12 . Although TTV DNA was present at high concentrations in liver tissue and in sera of patients with liver disease 13 , several studies have reported a high endemicity of infection in subjects with no evidence of hepatitis 14 . Therefore, the role of TTV as a causative agent of liver disease is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TTV was fi rst detected in subjects with post-transfusion hepatitis and indicated as a possible etiological source of non A-non C hepatitis 12 . Although TTV DNA was present at high concentrations in liver tissue and in sera of patients with liver disease 13 , several studies have reported a high endemicity of infection in subjects with no evidence of hepatitis 14 . Therefore, the role of TTV as a causative agent of liver disease is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Another recently described virus is the TT virus, a DNA virus seen associated with hepatitis in Japan, but questions still remain as to its significance (68,69).…”
Section: Other Virusesmentioning
confidence: 99%
“…To confirm these findings, we genetically characterized 420 clones of NG primer products from 32 thalassemia patients and 8 healthy individuals, as well as 50 PCR products amplified by TT and RD037/ 038/051/052 primers from 50 thalassemia patients and 96 TLMV-S primer product clones from 16 thalassemia patients. We detected TTV genotypes 1 to 3, 9 to 13,14,16,18,22,23, and group 5 (JT33F/JT34F/CT39F/CT44F); SENV genotypes A, B, D, and H; and four TLMV groups (three known plus one newly identified). TTV genotypes 4 to 8,15,17,19, and 20 including SENV (genotypes C and E to G) were not found, presumably due to their low prevalence in the test populations.…”
mentioning
confidence: 94%
“…TTV and TTLVs are widely distributed geographically, with an extremely high prevalence of viremia in the general population, particularly in tropical countries (32) and parts of Asia (6). Mixed-genotype infections are therefore common, particularly in thalassemia patients, due both to the high frequency of viral transmission through repeated therapeutic blood transfusions and the persistent nature of the viruses (5,9,14,15,18,23,31). TTV and TTLVs demonstrate an extremely wide range of sequence divergence.…”
mentioning
confidence: 99%